2021
DOI: 10.1007/s00405-021-06809-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing necrotizing external otitis on CT and MRI: assessment of pattern of extension

Abstract: Background and purpose Necrotizing external otitis (NEO) is a serious complication of external otitis. NEO can be classified according to—anterior, medial, posterior, intracranial, and contralateral—extension patterns. Currently there is no consensus on the optimal imaging modality for the identification of disease extension. This study compares NEO extension patterns on MR and CT to evaluate diagnostic comparability. Methods Patients who received a CT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…1) [25,26]. Van der Meer et al found that medial or intracranial spreading patterns can be best identified with MRI, whereas posterior spreading patterns solely based on cortical destruction of the mastoid and temporal bone were solely found by CT [27 ▪ ].…”
Section: Imagingmentioning
confidence: 99%
“…1) [25,26]. Van der Meer et al found that medial or intracranial spreading patterns can be best identified with MRI, whereas posterior spreading patterns solely based on cortical destruction of the mastoid and temporal bone were solely found by CT [27 ▪ ].…”
Section: Imagingmentioning
confidence: 99%
“…MRI is superior in evaluating soft-tissue extent, bone marrow involvement, and intracranial complications. Disease extension, progression, and complications during follow-up are best evaluated with MRI [ 13 , 14 ]. However, MRI findings always lag behind the clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of NEO patients described five different patterns of spread- anterior (most common, involving temporal bone and TMJ), medial (sphenoid bone, clivus, petrous apex, jugular foramen), posterior (mastoid temporal bone), intracranial and contralateral [40 ▪ ]. Different modalities were complementary in identification of these extension patterns, e.g., anterior pattern seen on both MR and CT, medial and intracranial better seen on MR and posterior pattern on CT [40 ▪ ].…”
Section: Extent Of Diseasementioning
confidence: 99%